Keberagaman Budaya dan Agama di Kota Manado - Frangky Suleman (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2017)
The term “Torang Samua Basudara” was the slogan of the community in North Sulawesi in order to keep social harmony and peace in the North Sulawesi. Through the symbol “torang samua basudara” it can built up through value meaning as a process, not as a result. So the peace in Manado city will stay awake.